Fatimids, crusaders and the fall of Islamic Jerusalem: Foes or allies? - Abu-Munshar, M.Y. (Taylor & Francis, 2010)
The fall of Islamic Jerusalem to the crusaders during the first Crusade created a sense of agitation and anger amongst Muslims as Islamic Jerusalem had been under their rule for centuries before. A considerable number of scholars have pointed at the Fatimids as the main cause of the fall of Islamic Jerusalem, claiming that the region would not have fallen had it not been for the alliance and collaboration between the Fatimids and the crusaders. This article is an attempt to present a critical analysis of the historical narratives of Muslim and non-Muslim historians who have continued to accuse the Fatimids of collaborating with the crusaders and depict them as the main cause of the fall of Islamic Jerusalem during the first Crusade. It also tries to answer the following two questions. Did the Fatimids really invite the crusaders to invade al-Sham? And is it true that the Fatimids misunderstood the crusaders' aims and targets?